CONTEMPORARY ECONOMIC CHALLENGES IN THE MUSLIM WORLD: A CRITICAL EVALUATION OF THE MODERN ECONOMIC SYSTEM IN LIGHT OF THE ISLAMIC OBJECTIVES OF SHARIAH (Al-Aasar, 2025)
The contemporary Muslim world faces multifaceted economic challenges, including persistent poverty, income inequality, high unemployment, financial instability, and reliance on interest-based systems. These issues are compounded by weak governance, inadequate institutional frameworks, and insufficient alignment between economic policy and ethical principles. This research critically evaluates the modern economic system in light of the Maqāṣid al-Sharīʿah (objectives of Islamic law), exploring how Islamic ethical and legal principles can inform sustainable, just, and socially inclusive economic practices.The study is structured into ten sections, each addressing key dimensions of economic challenges and their potential solutions. It highlights the contradictions between conventional interest-based finance and the Shariah objectives of justice (ʿadl), wealth preservation (ḥifẓ al-māl), social welfare (maṣlaḥah), and human dignity (karāmah al-insān). Risk-sharing financial models, including mudarabah and musharakah, are examined as viable alternatives, promoting equitable wealth distribution, ethical investment, and economic resilience. Redistributive mechanisms such as zakat, waqf, and inheritance laws are analyzed for their potential to alleviate poverty and reduce social inequality.The paper also emphasizes the crucial role of governance, institutional integrity, and accountability in implementing Shariah-compliant economic systems. Strong ethical oversight and participatory governance ensure transparency, reduce corruption, and align economic policy with public welfare objectives. Furthermore, the research addresses contemporary challenges such as global market pressures, institutional limitations, and the need for public awareness and education to enable effective participation in ethical economic systems.This study concludes that integrating Maqāṣid al-Sharīʿah principles into economic policy and institutional practice can create a resilient, inclusive, and morally grounded economic order. By combining ethical finance, redistributive mechanisms, governance reforms, and sustainable investment strategies, Muslim-majority countries can achieve long-term prosperity, social justice, and human development, ensuring that economic growth serves both material and ethical objectives.